Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(12x-5).(4x-1)-(3x-7).16x=81
48x²-12x-20x+5-(48x²-112x)=81
48x²-12x-20x+5-48x²+112x=81
(48x²-48x²)+(112x-12x-20x)+5=81
0+100x-20x+5=81
80x+5=81
80x=81-5
80x=76
x=76:80
x=19/20
Vậy x=19/20
Hok tốt
(12x - 5)(4x - 1) + (3x - 7)(1 - 16x) = 81
48x2 - 32x + 5 - 48x + 115x - 7 = 81
83x - 2 = 81
83x = 83
=> x = 1
(12x-5).(4x-1)+(3x-7).(1-16x) = 81
=> 48x2-12x-20x+5+3x-48x2-7+112x = 81
=> 83x-2 = 81
=> 83x = 81+2
=> 83x = 83
=> x = 83:83
=> x = 1
( 12x - 5 ) ( 4x -1 ) + ( 3x - 7 ) ( 1 - 16x ) = 81
48x2 - 12x - 20x + 5 + 3x - 48x2 - 7 + 112x = 81
83x = 81 - 5 + 7
83x = 83
x = 83/83
x = 1
Chúc bn hok tốt nha
Ta có : ( 12x - 5 ) ( 4x - 1 ) + ( 3x - 7 ) ( 1 -16x ) = 81
=> 48x2 - 20x - 12x + 5 + 3x - 7 - 48x2 + 112x = 81
=> 80x - 2 = 81
=> 80x = 83
=> x = 83/80
<=> 48x^2 - 12x - 20x + 5 + 3x - 48x^2 - 7 + 112x = 81
<=> -32x + 115x = 81 + 2
<=> 83x = 83
<=> x = 1
(12x - 5)(4x - 1) + (3x - 7)(1 -16x) = 81
48x2 – 12x – 20x + 5 + 3x - 48x2 – 7 + 112x = 81
83x – 2 = 81
83x = 83
x = 1